2020
DOI: 10.1002/mnfr.201900696
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Folate Status and Sperm Quality, Pregnancy Outcomes, and Epigenetics: A Systematic Review and Meta‐Analysis

Abstract: Scope: The effectiveness of maternal folate in reducing the risk of congenital malformations during pregnancy is well established. However, the role of the paternal folate status is scarcely investigated. The aim of this study is to investigate the evidence of associations between the paternal folate status and sperm quality, sperm epigenome, and pregnancy outcomes. Methods and results: Databases are searched up to December 2017 resulting in 3682 articles, of which 23 are retrieved for full-text assessment. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
17
0
6
Order By: Relevance
“…In addition, sperm from mice under a folate-deficient diet showed differential DNA methylation marks at genes implicated in development, diabetes, autism, and schizophrenia (Lambrot et al, 2013). In humans, several studies have reported on the relationship between paternal and/or maternal diet and sperm DNA methylation in male infertility (Shukla et al, 2014;Hoek et al, 2020;Toschi et al, 2020). A recent study conducted on infertile males who underwent oral supplementation with micronutrients in support of folate, B vitamins, zinc, and cysteines reported an increase in DNA methylation levels, resulting in improved sperm nuclear maturation and antioxidant defenses, with a possible positive effect on reproductive function (Bassiri et al, 2020).…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…In addition, sperm from mice under a folate-deficient diet showed differential DNA methylation marks at genes implicated in development, diabetes, autism, and schizophrenia (Lambrot et al, 2013). In humans, several studies have reported on the relationship between paternal and/or maternal diet and sperm DNA methylation in male infertility (Shukla et al, 2014;Hoek et al, 2020;Toschi et al, 2020). A recent study conducted on infertile males who underwent oral supplementation with micronutrients in support of folate, B vitamins, zinc, and cysteines reported an increase in DNA methylation levels, resulting in improved sperm nuclear maturation and antioxidant defenses, with a possible positive effect on reproductive function (Bassiri et al, 2020).…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Despite the exact relationship between diet and the epigenome remains unclear, several studies reported an association between epigenetic modifications and dietary depletion or supplementation (1,(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming clear that paternal factors may also have significant epigenetic implications 84,61 , and therefore become important when considering environmental causes of congenital malformations. This is particularly relevant given the increasing prevalence of intracytoplasmic sperm injection, which similarly subjects oocytes to foreign environments.…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%